Impact of the National Vaccination Strategy on the Prevalence of Streptococcus pneumoniae and Its Serotypes Among Clinically Healthy Children Under Six Years of Age During and After the COVID-19 Pandemic - Ivelina Trifonova; Victoria Levterova; Ivan Simeonovski; Magi Ivanova; Nadia Brankova; Todor Kantardzhiev (Vaccines)
Introduction: An effective vaccination strategy requires monitoring serotype changes by geography and age. This study analyzed Streptococcus pneumoniae serotypes in healthy children under 6 years of age vaccinated with PCV10 in Bulgaria from October 2021 to May 2025. Methods: A total of 569 children were screened for the lytA and cpsA genes viareal-time polymerase chain reaction (real-time PCR). Positive samples were typed using relevant kits, and 76 serotypes/serogroups of S. pneumoniae were identified. Results: Nasopharyngeal swabs from 232 children (40.8%) were found to carry S. pneumoniae, and a total of 255 serotypes were detected, with 19B/19C (17.2%), 6C (10.7%), and 15B/15C (9.8%) being the most prevalent. Of these, 91 serotypes (15.9%) were included in at least one vaccine, while the remaining 164 serotypes (25.4%) were not. The carriage rate reduced to 22% in 2023 but increased to 47% in 2024. Overall, younger children had lower carriage rates (p < 0.05), with serotype 6C being more common in children under 12 months of age (25%). Approximately 9.1% of pneumococcal carriage cases involved co-detected serotypes, with significantly higher co-detection rates for 19B/19C, 15B/15C, 10B, 10F/C, 23B, 7C/40, 23A, and 24A compared with mono-detection rates (p < 0.05). Conclusions: 19B/19C, 6C, 15B/15C, and 19A were identified as the main serotypes. Children over 3 years of age were also more likely to carry multiple pneumococci. These findings emphasize the need to reassess childhood vaccination strategies to curb the spread of antibiotic-resistant serotypes.